Control of the Faraday rotation via electromagnetically induced transparency medium and graphene metasurfaces. (3rd September 2019) - Khan, M Imtiaz; Ali, Tariq; Ali, Hazrat; Zubair, Muhammad; Ahmad, Iftikhar; Shafiq, Muhammad; Ahmad, Pervaiz; Rehman, Fida; Saeed, Yasir
Abstract: We investigate theoretically the control over Faraday rotation via an electromagnetically induced transparency medium (EIT) and graphene metasurfaces. The Faraday rotation of the light pulse is enhanced with increased probe field detuning. The increasing strength of the magnetic field enhances the rotation of the polarization plane and shifts its zero crossing at a higher frequency. The increase in the chemical potential rotates the polarization plane of the light pulse propagating through the system at low frequency. The periodic arrangement of disks on a graphene metasurface enhances the Faraday rotation of the light pulse and shifts the zero crossing relatively at a low frequency. The chemical potential, magnetic field and periodic length of disks can be used to control the Faraday rotation of light pulses at the desired frequency.